VARIATIONS AND EXPRESSION OF VERY LOW-DENSITY LIPOPROTEIN RECEPTOR (VLDLR) mRNA IN THE LIVER AND OVARY OF A LOW EGG PRODUCTION STRAIN OF LOCAL IRAQI HENS - D. H. Al-Hassani,; W. M. Razuki,; H. S. Abdulwahid, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This work was conducted to study the association of variations in the VLDLR gene and mRNA expression in the liver and the ovary of local Iraqi hens with some productive and blood traits. The VLDLR gene variations were studied using blood samples of 173 pedigreed hens, 47 weeks old while the expression was studied using tissue samples of the ovary and liver in 30 pedigreed hens, 60 weeks old. Genotypic and allelic frequencies, production traits, and biochemical serum blood were investigated. The results showed that the genotypic and allelic frequencies of the VLDLR in 173 chickens did not agree with Hardy-Weinberg equilibrium (P